2008
DOI: 10.1002/ajmg.b.30840
|View full text |Cite
|
Sign up to set email alerts
|

Association of SLITRK1 to Gilles de la Tourette Syndrome

Abstract: Previously the Slit and Trk-like family member 1 (SLITRK1) gene was identified as a candidate gene for Gilles de la Tourette Syndrome (GTS) based on a patient that carried a chromosomal inversion on 13q, as well as the identification of two rare DNA variants in the SLITRK1 gene. Since that report, studies have tested for the two rare variants in GTS and either did not find them, or when found, they did not segregate with the disorder in families, casting doubt on the relationship of this gene to GTS. We tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 16 publications
7
65
1
1
Order By: Relevance
“…Applying the transmission test for LD as implemented in Haploview, 18 we found SNPs rs9593835 and rs9546538 to be nominally associated with the disorder, whereas the same three-SNP haplotype as reported by Miranda et al 15 (haplotype TCT) was also over-transmitted in our sample (Table 1). Analysis by individual populations is shown in Supplementary Tables 2 and 3 and does not reveal heterogeneity among populations.…”
Section: Jmsupporting
confidence: 79%
See 3 more Smart Citations
“…Applying the transmission test for LD as implemented in Haploview, 18 we found SNPs rs9593835 and rs9546538 to be nominally associated with the disorder, whereas the same three-SNP haplotype as reported by Miranda et al 15 (haplotype TCT) was also over-transmitted in our sample (Table 1). Analysis by individual populations is shown in Supplementary Tables 2 and 3 and does not reveal heterogeneity among populations.…”
Section: Jmsupporting
confidence: 79%
“…None of the patients carried any of the variants reported by Abelson et al 2 However, significant associations with SNP rs9593835 as well as two three-marker haplotypes were identified, suggesting, for the first time, that there is a common TS risk factor of low penetrance in linkage disequilibrium (LD) with the associated marker and/or haplotypes. 15 The study concluded that confirmation studies were needed in order to support these preliminary findings.…”
Section: Jmmentioning
confidence: 96%
See 2 more Smart Citations
“…Several follow-up studies that screened for the observed SLITRK1 genetic changes in TS either failed to find them [39][40][41][42], or when identified, they did not segregate with the disorder in families [43,44], hence clouding the link between SLITRK1 and TS. In this context, the original authors rejected claims of confounding population stratification between cases and controls [45], and recent studies by us and other groups have re-highlighted the significance of the initial findings by demonstrating a strong over-transmission of alleles and/or haplotypes of SLITRK1 to affected individuals [46][47][48]. All in all, there is a consensus that the TS gene discovery story has had a promising start.…”
Section: Ts Gene Discovery: Contained Excitement?mentioning
confidence: 99%